Facts and artefacts : art in the Islamic world : festschrift for Jens Kröger on his 65th birthday - Kröger, Jens; Hagedorn, Annette; Shalem, Avinoam (Islamic history and civilization ;, 2007)
The scholarly search on the art of the object is of enduring interest and enjoys a new renaissance in the last few years. This book mainly explores the art and craft of Islamic artefacts and presents to the reader a diverse range of approaches. Despite this variety, in which also artefacts of the pre-Islamic, period as well as 'orientalized' European artefacts of the modern era are included, there is an overarching theme - the linking of the interpretation of objects and their specific aesthetics to textual sources and the aim of setting them in historical and artistic context. In this impress.